3D Modeling of CO2 Geological Storage of Songkhla Sub-Basins in the Lower Gulf of Thailand - Choomkong, Apichat; Sirikunpitak, Siriphat; Temkiatvises, Nattaphon; Yordkayhun, Sawasdee (International Journal of Integrated Engineering, 2020)
The CO2 geological storage of is a one high efficiency for CO2 disposal method from the energy sector especially production of electricity by using fossil fuels. This method can help mitigate global warming will be occurring. The first aim of article to study a construction 3D geological model for assessment CO2 storage capacity and direction of CO2 movement, case in the Songkhla Sub-basins in the Lower Gulf of Thailand. The Sonkhla sub-basins consist of Bua-Ban, Benjarong and Songkhla. In the article focus on Bua-Ban was devided by Songkhla Lower Miocene (SLM) and Songkhla Lower Oligocene (SLO). 3D geological CO2 storage model of sites were constructed by a public data that will be accessed like a data consist of a depth structure map, geologic setting and reservoir properties. The second aims to study a risk of seismic hazard from CO2 injection by planning multi wells CO2 injection in the reservoir. As the results, the accumulation of CO2 storage capacity from 3D geological model from SLM and SLO approximate 5.69 Mton-CO2 based on 3D geological model was constructed by limit of data. 3D geological model can be used to investigation CO2 migration and pressure build up in the reservoir during CO2 injection on time lapse for protection risk of CO2 leaking out of reservoir. In addition, Songkhla sub-basins which site safety for seismic induced and effective geological CO2 storage based on injection rate of CO2 undertaken initial pressure.